Two new species of the genus Assamacris (Orthoptera: Acrididae: Catantopinae) from Yunnan, China - Mao, Ben-Yong; Ren, Guo-Dong; Ou, Xiao-Hong (Zootaxa, 2007)
This paper reports on two new species of the genus Assamacris Uvarov, 1942, namely A. trimaculata sp. nov. and A. bidentata sp. nov., from Yunnan, China. All type specimens are deposited in the College of Life Sciences and Chemistry, Dali University (CLDU). A revised generic diagnosis and a key to known species are given.